Seventeenth International Conference on Thermoelectrics. Proceedings ICT98 (Cat. No.98TH8365)
DOI: 10.1109/ict.1998.740449
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties in (Na,Ca)Co/sub 2/O/sub 4/ ceramics

Abstract: The resistivity and thermopower of polycrystalline Na 1.1−x Ca x Co 2 O 4 were measured and analyzed. Both the quantities increase with x, suggesting that the carrier density is decreased by the substitutions of Ca 2+ for Na + . Considering that the temperature dependence of the resistivity show a characteristic change with x, the conduction mechanism is unlikely to come from a simple electronphonon scattering. As a reference for NaCo 2 O 4 , single crystals of a two-dimensional Co oxide Bi 2−x Pb x M 3 Co 2 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Because of their composite structure and their large thermopower values, the misfit bismuth based cobaltites have been recently the focus of attention [1][2][3]. These materials have an unusual combination of properties: despite their metallic character with relatively low resistivity, they have rather large Seebeck coefficient ∼+100 µV K −1 , which makes them very promising materials for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their composite structure and their large thermopower values, the misfit bismuth based cobaltites have been recently the focus of attention [1][2][3]. These materials have an unusual combination of properties: despite their metallic character with relatively low resistivity, they have rather large Seebeck coefficient ∼+100 µV K −1 , which makes them very promising materials for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Following NaCo 2 O 4 , other layered cobalt oxides, CaCo-O [5,6,7,8], Bi-Sr-Co-O [9,10,11], Tl-Sr-Co-O [12] have been found to show good thermoelectric performance. In particular, Funahashi et al [8] showed ZT > 1 at 1000 K for Ca-Co-O.…”
Section: Introductionmentioning
confidence: 99%
“…1 In recent years, "misfit-layered cobalt oxides" have been highlighted as next-generational TE materials. [2][3][4][5][6] The members of this material family possess a crystal structure consisting of alternate stacks of a hexagonal CoO 2 layer ͑of the CdI 2 structure͒ and a multi-square-plane layer, M m A 2 O 2+mϮ ͓of the rock-salt ͑RS͒ structure͔. The general chemical formula may be given by ͓M m A 2 O 2+mϮ ͔ q CoO 2 ͑M = Bi, Pb, Co, etc., A = Ba, Sr, etc., m =0, 1, or 2͒, where q is the ratio of b-axis lengths of the two layers, i.e., q ϵ b CoO 2 / b RS .…”
Section: Introductionmentioning
confidence: 99%